Transforming Vocational School and Industry Partnerships from Administrative to Managerial Practices: A Planning, Organizing, Actuating, and Controlling Multi-Site Study - Suharsoyo, Tjipto; Khamidi, Amrozi; Hariyati, Nunuk (Journal of English Language and Education, 2026)
Many partnerships between vocational high schools (SMK) and industry (DUDI) remain limited to formal administrative arrangements such as Memorandums of Understanding (MoUs), without effective managerial governance. As a result, these collaborations often have limited impact on graduate employability. This study analyzes how managerial functions—planning, organizing, actuating, and controlling (POAC)—shape the effectiveness and sustainability of school–industry partnerships in Indonesia and proposes an adaptive partnership management model. This research employed a qualitative comparative multi-site design involving two private vocational schools in Mojokerto, Indonesia. Data were collected through in-depth interviews with 27 key informants, supported by alumni data (n=87), participatory observations, and document analysis. Data validity was ensured through source and methodological triangulation. The findings reveal two partnership archetypes: (1) the Gradual Collaborative Model, characterized by value-based planning, formal structures, and institutionalized governance; and (2) the Adaptive Operational Model, which demonstrates strong operational flexibility but limited strategic documentation. Based on these findings, the study proposes an Adaptive-Strategic Partnership Model that integrates POAC managerial functions, collaborative governance principles, and outcome-based evaluation within a dynamic partnership cycle. The novelty of this research lies in reconceptualizing classical management theory in the context of inter-organizational educational partnerships and proposing a tiered DUDI engagement typology as a strategic instrument for strengthening vocational education governance.